Quantificação de biomassa e de carbono orgânico na regeneração natural de floresta ombrófila mista - Nova Prata, RS - Medeiros, Janize Augusta Ferro de (2004)
This work had as objectives to ajust mathematical models that describe, through equations, the biomass volume and the concentration of organic carbon of the natural regeneration of Mixed Shade Tolerant Forest. To reach the objectives two sample units of 10m of width by 50m of length had been installed, totaling 1000m2.Each unit was subdivided in 5 subunits of 10 x 10m. The biomass was quantified by sampled area and the individuals had been divided in three categories: plantule (plants with superior height to 0,50m, and that to 1,30m having less than 3cm of CAP), regeneration 1 (CAP ≥ 3 and <15cm) and regeneration 2 (CAP ≥ 15 and < 30cm).The data had been collected in a destructive way. Besides the weights of each fraction (stem, branches, leaves, roots and miscellany), CAP, total heights and first alive branch were measured, cup diameter and the procedure of cubic measure stem had been done. The fine litter was determined in areas of 1m2, and the thick in 9m2 in each subunit. In the determination of the dry biomass and carbon contents, it had been collected samples of each fraction, and dried up in greenhouses with temperature of 75ºC until obtaining constant weight. To verify the relationships between the humid biomass and the dendrometric variables it had been used the Pearson Correlation Coefficient and graphic analysis. In the verification of the adequacy of the humid biomass models, the determination coefficient statistics had been analyzed, estimate standard error, F significant value, t value for the coefficients and the residues distribution. In the model construction for the dry biomass quantification, the weight of the humid biomass had been used as an independent variable. In the verification of the adequacy of the dry biomass models, the determination coefficient statistics, estimate standard error and graphic analysis for the residues had been analyzed. For the models construction (humid and dry biomass), the procedure statistical stepwise had been adopted, in which the potentials independent variables had been selected in 5% level of error. In the verification of the observed values had been significantly difference from the estimated values, the χ2 test had been used. The equations to esteem the humid biomass presented good adjustment with high values of determination coefficient, low estimate standard error and good residues distribution. The dry biomass had been presented linear or quadratic relationship in relation to the humid biomass and the equations presented good adjustment, with high values of determination coefficient, low estimate standard error and good distribution between the observed and fitting values. In the organic carbon estimate it had been used the medium contents found in the samples as multiplication factor. The total of the natural regeneration biomass had been 31.629,600 kg/ha, (regeneration 2 represented 46%, regeneration 1 45% and plantules 9%) and the litter had been accumulated 26.606,000 kg/ha, (54% corresponded to fine litter and 46% thick litter). The regeneration had been accumulated 7.517,869 kg/ha of organic carbon, (regeneration 2 contributed with 46,61%, regeneration 1 with 44,41% and plantules with 8,98%) and the litter had been stocked 5.509,067 kg/ha. The analysis of the three strata with the stem fraction had been contributed with 52,43% of the stocked organic carbon, branches 22,66%, roots 17,39%, leaves 5,27% and miscellany 2,25%.